Diagnosis of the gifted in Israel. (January 2014) - David, Hanna
Many parents of gifted, talented and high-ability children seek counseling in the belief that a diagnosis of their child as 'gifted' will solve the problems they and their child are encountering. In Israel, most children are screened for giftedness using the Szold examinations in grade 2 or 3 between the ages of 7 and 9 years. The Szold test screens for mathematical–logical and verbal abilities, but it does not screen for creativity. In the letter of 'acceptance/rejection', the only information given is whether or not the child is entitled to participate in the local program for the gifted. In this article I will endeavor to explain why it is not always desirable or necessary to seek an additional clinical diagnosis of potential ability because the problems expressed by both parents and children derive from emotional causes, particular learning disabilities or a mismatch between the child's potential and the level of curricula provision.